Testing men's hormone responses to playing League of Legends: No changes in testosterone, cortisol, DHEA or androstenedione but decreases in aldosterone. (June 2018) - Gray, Peter B.; Vuong, Jimmy; Zava, David T.; McHale, Timothy S.
Abstract: Esports, or competitive video gaming, has rapidly increased in online play and viewing. The popularity of esports such as League of Legends may derive in part because it features skills-based coalitional competition. Whereas a sizable literature focuses on adult human hormones and competition, little research has addressed the hormone responses of men playing video games. The purpose of the present study is to investigate the effects of playing a coalitionary-based esport on young U.S. men's steroid hormone levels in a naturalistic study. We tested salivary steroid changes in response to esports club members (n = 26) playing League of Legends against other people and the computer. We hypothesized that esports competition would increase testosterone, cortisol, DHEA and androstenedione levels, with more pronounced increases in winners than losers. Participants provided saliva samples before and after competitions lasting 15–27 min in duration. Salivary testosterone, cortisol, DHEA and androstenedione levels did not change overall or between play against people vs. the computer or with respect to winning or losing. However, play duration (range 16–27 min) was positively related to changes in DHEA, androstenedione and testosterone during play against people. Aldosterone levels decreased overall. We suggest that the informal and familiar environment as well as relatively short play duration help account for generally null findings. These findings help document physiological effects of esport play, in turn contributing to a richer understanding of why so many play and watch esports. Highlights: This is the first study to test hormone effects of playing League of Legends. Young men's testosterone, cortisol, DHEA and androstenedione did not change. Aldosterone levels decreased during play, both against humans and computer. Testosterone, DHEA and androstenedione change correlated with play duration.